An Analysis of Three Pistacia Species’ Phenolic Compounds and Their Potential Anticancer and Cytotoxic Activities on Cancer Cells—A Review - Naser A. Alsharairi (Current Issues in Molecular Biology, 2025)
The genus Pistacia from the Anacardiaceae family contains species of wild flowering plants. The only species that produces edible nuts large enough for commercial sale is P. vera L. (pistachio). Other species, such as P. terebinthus L., P. atlantica L., and P. khinjuk, are used as pistachio rootstocks. Pistacia species include phenolic compounds, such as flavonoids, essential oils, and tannins, which are responsible for a number of pharmacological properties. The species most commonly investigated for their anticancer and/or cytotoxic activities against cancer cells in experimental studies include P. lentiscus, P. atlantica subspecies, and P. chinensis subsp. integerrima. However, no review exists that evaluates the phenolic compounds of three other Pistacia species (P. vera L., P. terebinthus L., and P. khinjuk) and their anticancer and cytotoxic effects. Thus, this review aims to thoroughly assess the phenolic compounds that were isolated from these species and investigate any potential anticancer or cytotoxic effects on cancer cells. The findings show that pistacia species and their isolated phenolic compounds (phenolic acids, flavonoids, and essential oils) from different plant parts have anticancer activity against lung, cervical, prostate, gastric, colon, liver, renal, skin, and breast cancer cells. Additionally, certain phenolic compounds from pistacia species have cytotoxic activity; however, the degree of toxicity may vary based on the dosage and duration of use. Further experiments are required to fully understand the possible mechanisms underlying the anticancer and cytotoxic effects of pistacia species and their phenolic compounds on cancer cells.